Ceramica contemporanea d’autore in Italia - Pirozzi, Francesca (Clio, 2024)
The central topic of the book is contemporary ceramic art production in Italy, which is explored and analyzed in all declinations in order to illustrate the methodological models adopted by artists and designers. In particular, the investigation aims at tracing a paradigmatic sampling of ceramic art making and to identify the most significant contemporary experiences for each approach. The research strategy adopted is case study and it is supported by indirect and direct sources, including the testimonies of the protagonists. The analysis of creative dynamics also permits to deal with some modern aesthetics issues, such as the relationship between art and technique, the hierarchy between forms of expression, the gender issues, the relationship between art, industry and craft, and artistic communication. Thus, through the dialectical comparisons between the cases examined and their exposition in chronological order, the study retraces salient moments in the history of Italian contemporary fictile art.